NOX proteins and ROS generation: role in invadopodia formation and cancer cell invasion - Nelson Quilaqueo-Millaqueo; David A. Brown-Brown; Jetzabel A. Vidal-Vidal; Ignacio Niechi (Biological Research)
Abstract NADPH oxidases (NOX) are membrane-bound proteins involved in the localized generation of reactive oxygen species (ROS) at the cellular surface. In cancer, these highly reactive molecules primarily originate in mitochondria and via NOX, playing a crucial role in regulating fundamental cellular processes such as cell survival, angiogenesis, migration, invasion, and metastasis. The NOX protein family comprises seven members (NOX1-5 and DUOX1-2), each sharing a catalytic domain and an intracellular dehydrogenase site. NOX-derived ROS promote invadopodia formation, aberrant tyrosine kinase activation, and upregulation of matrix metalloproteinases (MMPs). Specifically, NOX5 modulates adhesion, motility, and proteolytic activation, while NOX1 likely contributes to invadopodia formation and adhesive capacity. NOX2 and NOX4 are implicated in regulating the invasive phenotype, expression of MMPs and EMT markers. DUOX1-2 participate in epithelial-mesenchymal transition (EMT), crucial for invasive phenotype development. Soluble molecules such as TGF-β and EGF modulate NOX protein activation, enhancing cell invasion through localized ROS production. This review focuses on elucidating the specific role of NOX proteins in regulating signaling pathways promoting cancer cell spread, particularly EMT, invadopodia formation and invasive capacity.